2023
DOI: 10.1007/s00253-023-12596-z
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoclusters with Ag2+/3+ oxidative states are a new highly effective tool against phytopathogenic bacteria

Abstract: The main measure worldwide adopted to manage plant bacterial diseases is based on the application of copper compounds, which are often partially efficacious for the frequent appearance of copper-resistant bacterial strains and have raised concerns for their toxicity to the environment and humans. Therefore, there is an increasing need to develop new environmentally friendly, efficient, and reliable strategies for controlling plant bacterial diseases, and among them, the use of nanoparticles seems promising. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Through a transcriptomic approach carried out on the P. syringae pv. tomato strain used in the study of Orfei et al ( 2023a ), whose genome we recently sequenced (Orfei et al 2023b ) to better perform the transcriptomic analysis, we demonstrated that the exposition of bacterial cells for 10 and 30 min at sub-letal doses of Argirium - SUNCs induced change in the expression of genes associated with transporters ( e . g ., CadA P-type ATPase, the arsenite resistance efflux pump, multidrug resistance proteins), iron homeostasis ( e .…”
Section: Silver Ultra Nano Clusters ( Argirium - ...mentioning
confidence: 71%
See 3 more Smart Citations
“…Through a transcriptomic approach carried out on the P. syringae pv. tomato strain used in the study of Orfei et al ( 2023a ), whose genome we recently sequenced (Orfei et al 2023b ) to better perform the transcriptomic analysis, we demonstrated that the exposition of bacterial cells for 10 and 30 min at sub-letal doses of Argirium - SUNCs induced change in the expression of genes associated with transporters ( e . g ., CadA P-type ATPase, the arsenite resistance efflux pump, multidrug resistance proteins), iron homeostasis ( e .…”
Section: Silver Ultra Nano Clusters ( Argirium - ...mentioning
confidence: 71%
“…The recent results we obtained with the nanomaterial silver ultra nanoclusters (< 2 nm) ( Argirium - SUNCs ® ), published in Applied Microbiology and Biotechnology (Orfei et al 2023a ), seem to open up new perspectives in the chemical control of plant bacterial diseases, which will be described in the present minireview.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The spread of microorganisms multi-resistant to antibiotics has reached significant numbers, so much so that the development of substances with innovative antimicrobial activity appears to be an urgent necessity. Argirium SUNc ® could be proposed as such, as, to date, there are no formulations on the market that present a broad effectiveness at a low concentrations (<2.5 ppm) and with little environmental impact [39][40][41][42][43][44]. In fact, they are synthesized using patented methods (EU-Pathent) which involve the use of biocompatible ingredients; consequently, the introduction of harmful substances is not foreseen and the concentrations in use do not exceed the limits established by laws.…”
Section: Discussionmentioning
confidence: 99%